Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4149/neo_2009_03_252
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and melatonin in prevention of female rat mammary carcinogenesis

Abstract: The present experiment aims to evaluate tumor suppressive effects of a selective inhibitor of cyclooxygenase-2 (COX-2) celecoxib (Celebrex, Pfizer) administered alone and in combination with melatonin in the prevention of N-methyl-N-nitrosourea (NMU)-induced mammary carcinogenesis in Sprague-Dawley female rats. Celecoxib was administered daily at a concentration of 1.666 g/kg diet to two groups during 20 weeks (starting a week before first NMU application). A combination of celecoxib and melatonin applied in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Abou-Issa et al (2001) reported inhibition in DMBA-induced mammary carcinogenesis in female Sprague-Dawley rats by celecoxib (0.25 g kg −1 , 0.50 g kg −1 , 1.00 g kg −1 or 1.50 g kg −1 diet) administered with diet. Similar results yielded our group -decrease in tumor incidence and frequency per animal and group was found during 20-week administration of celecoxib (1.67 g kg −1 chow) in NMUinduced mammary carcinogenesis; co-administration of melatonin reinforced the effect of celecoxib (Orendáš et al 2009). …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Abou-Issa et al (2001) reported inhibition in DMBA-induced mammary carcinogenesis in female Sprague-Dawley rats by celecoxib (0.25 g kg −1 , 0.50 g kg −1 , 1.00 g kg −1 or 1.50 g kg −1 diet) administered with diet. Similar results yielded our group -decrease in tumor incidence and frequency per animal and group was found during 20-week administration of celecoxib (1.67 g kg −1 chow) in NMUinduced mammary carcinogenesis; co-administration of melatonin reinforced the effect of celecoxib (Orendáš et al 2009). …”
Section: Discussionsupporting
confidence: 71%
“…Our group proved the chemopreventive effects of indomethacin administered in drinking water (Môci-ková-Kalická et al 2001), nimesulide applied subcutaneously (Kubatka et al 2002), rofecoxib (Kubatka et al 2003), etoricoxib (Orendáš et al 2007), and celecoxib (Orendáš et al 2009), all administered in the diet to female Sprague-Dawley rats with chemically-induced mammary tumors. Generally, at least 90% of mammary tumors showed malignant features, cribriform carcinoma in situ and invasive adenocarcinomas prevailed; the malignant/benign tumor ratio maintained regardless of oncostatic efficacy (Orendáš et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found a single long-term administration of PIO (Bojková et al, 2010) and MT to decrease mammary tumour incidence and frequency; PIO also positively altered tumour histopathological profile (Bojková et al, 2010). MT enhanced the mammary tumour growth inhibition of other substances: retinoids Bojková et al, 2000;Orendáš et al, 2012), NSAIDs (Kubatka et al, 2002;Orendáš et al, 2009), selective oestrogen-receptor modulators (Kubatka et al, 2001a(Kubatka et al, , 2001b and resveratrol (Kisková et al, 2012). In all these experiments, however, a standard-type diet was used (3-4% of total fat).…”
Section: Discussionmentioning
confidence: 94%
“…The anticancer effects of various chemopreventive agents [1][2][3][4][5][6]or their combinations with chemotherapeutic drugs [7][8][9][10][11] have been studied extensively.…”
mentioning
confidence: 99%